2006
DOI: 10.1007/s00125-006-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines as risk factors for type 2 diabetes: results from the MONICA/KORA Augsburg study, 1984–2002

Abstract: Aims/hypothesis: The chemokines monocyte chemoattractant protein-1 (MCP-1), IL-8 and interferon-γ-inducible protein-10 (IP-10) are released by adipocytes and appear to be involved in atherosclerosis. We hypothesised that these chemokines may be risk factors for the development of type 2 diabetes. Subjects and methods: Using a case-cohort design based on data from the population-based Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA)/Kooperative Gesundheitsforschung in der Region Augsburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 33 publications
(41 reference statements)
1
114
1
Order By: Relevance
“…On this source population, we applied a case-cohort study consisting of a random sample (called subcohort; nZ1885) of the source population stratified by sex and survey, and all incident T2DM cases (nZ555) in the source population diagnosed up to December 31, 2002 as it was described more detailed previously (31,(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…On this source population, we applied a case-cohort study consisting of a random sample (called subcohort; nZ1885) of the source population stratified by sex and survey, and all incident T2DM cases (nZ555) in the source population diagnosed up to December 31, 2002 as it was described more detailed previously (31,(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, high levels of many inflammatory factors at baseline in diverse human populations are correlated with incident T2DM, regardless of the initial degree of insulin resistance and obesity. Prospective studies have identified white blood cell count [12,15], pro-inflammatory cytokines [16], chemokines [17], and other several indirect markers of inflammation such as fibrinogen, sialic acid and PAI-1 [15,18] as predictors of T2DM. In contrast to all these inflammatory biomarkers, CRP measurement is less expensive, standardized and widely available.…”
Section: Inflammatory Markers For Development Of T2dm In Obese Patientsmentioning
confidence: 99%
“…The design of this prospective casecohort study [22], conducted within the population-based MONICA/KORA cohort, has recently been described in detail [23][24][25][26][27][28]. For detailed information on the study population see the Electronic supplementary material (ESM).…”
Section: Study Populationmentioning
confidence: 99%